Business Plan for M-Rupee Services, Mobile Banking Business in India - Manjunath, Gowtham; Dayma, Veejay; Lalwani, Vinay (2010)
The M-Rupee mobile banking business correspondent model has been envisaged as a service that shall cater largely to the rural population of India, a market segment which has witnessed extremely low penetration levels towards the achievement of complete financial inclusion. Traditional banking channels have witnessed extremely low penetration levels in this segment due to a number of reasons. This business solution has been structured to provide basic banking services at low costs. Mobile banking has created a fresh buzz in the Indian banking sector. Most of the commercial and non-commercial banks are finding effective ways to tap the Indian rural population, some unbanked and others banked who seldom use the banking facility. The mobile banking (also called as m-banking) industry has been a relatively new market in India and rest of the world. With the constantly increasing penetration of mobile phones in the rural parts of India, the present tele-density of India is more than 45%. The banking industry has been very successful in the recent years with reduced NPAs (Non-Performing assets) and increased net-profits. The market analysis shows that India has 215 million people who are potentially bankable. Only the public-private and nationalised banks have been operating in the rural areas with high servicing costs. Mostly rural people depend on informal financial sources such as money lenders, Self-Help groups etc. due to the lack of infrastructure and proximity to banking services. The main reasons for not using formal banking were usability and accessibility concerns. Thus the central government has been forcing the banks to look at and create low cost banking solution as a part of financial inclusion initiative. M-Rupee will position itself as a low-cost banking service for the banks, and will propose to deliver convenience and accessibility to the rural banking needs. The transactions will be charged with nominal amounts which will compensate for service expediency. Marketing program is designed to educate the rural customers regarding the usefulness and advantages of the service. The operational strategy involves designing of the entire functional and technical architecture to develop a robust and secure system. M-Rupee will be built on „Secure-SMS‟ platform and will associate with one of the well known Information Technology Solutions provider to build the system. The primary objective of the business is to achieve financial inclusion by maximising the use of existing assets and increasing the market share. The business strategy will involve collaborating with a bank through joint venture, which will enable financial access and also meet the regulatory guidelines of RBI. The entire project is expected to be implemented in phases. The initial pilot and implementation phases will take place in the Nashik district of Maharashtra. This is an ideal place to launch M-Rupee services, with the market research showing 210,000 potential customers in one district alone. Although there are few small players in the market, none of them are based on agent-network model.